Melampaui Tradisi: Jejak Penyebaran Metode Amtsilati dalam Dialektika Pembelajaran Kitab Kuning di Indonesia 2002-2020 - Al Haramein, Muhammad Mulky (Universitas Muhammadiyah Prof. Dr. Hamka, 2026)
This study is motivated by the concern of KH. Taufiqul Hakim regarding students’ difficulties in mastering nahwu and sharaf as essential foundations for understanding classical Islamic texts (kitab kuning). In 2001, he initiated the development of the Amtsilati Method as a systematic and structured approach designed to accelerate students’ ability to read and comprehend classical Islamic literature effectively. This research aims to analyze the historical background of the method’s emergence, its dissemination patterns, and the role of the founder and student networks in sustaining and expanding its influence. The study applies the historical method, including stages of heuristics, source criticism, interpretation, and historiography, combined with a descriptive-analytical approach. The findings reveal that since its official introduction in 2002, the Amtsilati Method has developed progressively through the founder’s central leadership, reinforced by the formation of regional coordinators, student associations, and alumni networks across Indonesia and abroad. These findings demonstrate that the Amtsilati Method constitutes not only a pedagogical innovation but also a structured and sustainable pesantren-based Islamic literacy movement.